Twin High-Resolution, High-Speed Imagers for the Gemini Telescopes: Instrument Description and Science Verification Results - Scott, Nicholas J.; Howell, Steve B.; Gnilka, Crystal L.; Stephens, Andrew W.; Salinas, Ricardo; Matson, Rachel A.; Furlan, Elise; Horch, Elliott P.; Everett, Mark E.; Ciardi, David R.; Mills, Dave; Quigley, Emmett A. (Frontiers in Astronomy and Space Sciences, 2021)
Two new imaging instruments, `Alopeke and Zorro, were designed, built, and commissioned at the Gemini-North and Gemini-South telescopes in 2018 and 2019, respectively. Here we describe them and present the results from over a year of operation. The two identical instruments are based on the legacy of the DSSI (Differential Speckle Survey Instrument) instrument, successfully used for years at the WIYN and the Gemini telescopes in Hawaii and Chile. `Alopeke and Zorro are dual-channel imagers having both speckle (6.7$''$) and ``wide-field'' ($\sim 1$ arcminute) field-of-view options. They were built to primarily perform speckle interferometry providing diffraction-limited imagery at optical wavebands, yielding astrometric separation uncertainties of $±$ 0.21 mas, position angle uncertainties of $±$ 0.7$^{°}$, and photometric uncertainties of $Δ$m $±$ 0.02-0.04 magnitudes (for the blue and red channels, respectively). One of their main scientific roles is the validation and characterization of exoplanets and their host stars as discovered by transit surveys such as the NASA Kepler, K2, and TESS missions. The limiting magnitude for speckle observations at Gemini can be quite faint ($r\sim$18 in good observing conditions) but typically the observed targets are brighter. The instruments can also function as conventional CCD imagers providing a 1 arc-minute field of view and allowing simultaneous two-color, high-speed time-series operation. These resident visitor instruments are remotely operable and are available for use by the community via the peer-reviewed proposal process.